As If It Were : Poems - Chappell, Fred, 1936- (Book collections on Project MUSE., 2019)
Inspired by ancient, modern, and contemporary writings, this author's sprightly new collection of verse presents tales, anecdotes, pointed stories, and aphorisms to spark the conscience of readers young and old. Playful and even zany, the humor in these poems pulls readers into a world filled with noble lions, crafty foxes, predacious wolves, longsuffering asses, and fashionable peacocks. The author illustrates how the fable offers a timeless form of wisdom, surprising us with revelations that challenge what we think we already know, along with fresh observations of daily experiences.